Strengthening Religious Characters Of Early Childhood Through Religious Practice - Errifa Susilo (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2020)
This research aimed to describe religious practices as strengthening religious characters in early childhood at Al Asror Tulungagung Integrated Islamic Kindergarten. This research used a qualitative research method with descriptive type of research in which this research studies thoroughly the application of religious practices in strengthening religious characters. Data collection techniques used interviews, observation and documentation. The informants in this research included the head of the institution and teachers at the Al Asror Integrated Islamic Kindergarten, Tulungagung. The results of the research on religious characters that are formed in the implementation of religious practices are (1) the practice of pronouncing Asma'ul Husna forms the religious character of obedient children in knowing the names of Allah which must be applied in everyday life; (2) The practice of murojaah of short surah and the practice of daily prayers form the character of discipline, helpful, polite, friendly, honest, and responsible; (3) The practice of dhuhur prayer in congregation forms the religious characters of children who are obedient in worshiping on time, responsibility, discipline, and order starting from the movement and reading in accordance with the Sharia (Islamic law); (4) The practice of commemorating Islamic holidays forms the religious character of exemplary children by imitating good behavior, courtesy, honesty, responsibility, discipline, trust.